(untitled) (Journal of Partial Differential Equations, 2019)
This paper studies the second-generation interpolating wavelet collocation methods in space and different Euler time stepping methods for parabolic problems. The convergence and stability are investigated. The operators are formulated using an efficient and exact formulation. The numerical results verify the efficiency of the methods.